Aneugen Versus Clastogen Evaluation and Oxidative Stress-Related Mode-of-Action Assessment of Genotoxic Compounds Using the ToxTracker Reporter Assay. (3rd July 2020) - Brandsma, Inger; Moelijker, Nynke; Derr, Remco; Hendriks, Giel
Abstract: Understanding the mode-of-action (MOA) of genotoxic compounds and differentiating between direct DNA interaction and indirect genotoxicity is crucial for their reliable safety assessment. ToxTracker is a stem cell-based reporter assay that detects activation of various cellular responses that are associated with genotoxicity and cancer. ToxTracker consists of 6 different GFP reporter cell lines that can detect the induction of DNA damage, oxidative stress, and protein damage in a single test. The assay can thereby provide insight into the MOA of compounds. Genotoxicity is detected in ToxTracker by activation of 2 independent GFP reporters. Activation of the Bscl2-GFP reporter is associated with induction of DNA adducts and subsequent inhibition of DNA replication and the Rtkn-GFP reporter is activated following the formation of DNA double-strand breaks. Here, we show that the differential activation of these 2 genotoxicity reporters could be used to further differentiate between a DNA reactive and clastogenic or a non-DNA-reactive aneugenic MOA of genotoxic compounds. For further classification of aneugenic and clastogenic compounds, the ToxTracker assay was extended with cell cycle analysis and aneuploidy assessment. The extension was validated using a selection of 16 (genotoxic) compounds with a well-established MOA. Furthermore, indirect genotoxicity related to the production of reactive oxygen species was investigated using the DNA damage and oxidative stress ToxTracker reporters in combination with different reactive oxygen species scavengers. With these new extensions, ToxTracker was able to accurately classify compounds as genotoxic or nongenotoxic and could discriminate between DNA-reactive compounds, aneugens, and indirect genotoxicity caused by oxidative stress.